Evaluating Urban Village Fund Management: An Analysis of Planning, Budgeting, Implementation, Guidance, and Supervision - Saharuddin (Pusbindiklatren Bappenas, 2024)
The management of urban village development is currently ineffective, as evidenced by deficiencies in planning, budgeting, implementation, development, and supervision. Additionally, there is a notable shortfall in the quality and quantity of human resources, compounded by inadequate involvement of regional technical officials in providing assistance and guidance. This policy paper aims to review, identify, analyze, and formulate policy recommendations to better integrate the roles of communities and community groups in urban village development. The study employed a normative qualitative approach, utilizing in-depth interviews with Village Heads and community group leaders who are directly involved in village activities and have relevant insights. Data were collected through interviews, empirical studies, and documentary analysis. The findings indicate that implementing activities related to urban village facility and infrastructure development, as well as community empowerment, is “less effective.” Consequently, it is recommended that the Makassar City Mayor Regulation Number 28 of 2020 be revised to provide more detailed guidelines for community or community-group-based activity management.